Vitamin D deficiency in a Portuguese epilepsy cohort: who is at risk and how to treat. Issue 2 (15th June 2021) - Cunha, Inês Antunes; Saraiva, Ana MR.; Lopes, Pedro; Jesus‐Ribeiro, Joana; Duarte, Cátia; Leitão, Fátima; Sales, Francisco; Santana, Isabel; Bento, Conceição
Abstract: Objective . The epilepsy‐related risk factors for vitamin D deficiency, particularly the use of enzyme‐inducing antiepileptic drugs (EIAEDs), and how to treat vitamin D deficiency in patients with epilepsy remain unclear. Our aims were to explore risk factors and the influence of EAIEDs in vitamin D status and to determine the efficacy of a daily dose of oral cholecalciferol (vitamin D3) in epileptic patients with vitamin D deficiency. Methods . Clinical data were collected and 25‐hydroxyvitamin D (25(OH)D) serum levels were measured. All patients with vitamin D deficiency (25(OH)D .20 ng/mL) or insufficiency (25(OH)D from 21‐29 ng/mL) were treated with 6, 670 IU/day cholecalciferol for eight weeks and 25(OH)D was then remeasured. Descriptive and inferential statistics were employed. Results . A total of 92 patients (44.6% males), with mean age of 41.0±14.8 years, were included. Measurements of 25(OH)D revealed that 79.3% patients had abnormal levels: 56.5% were vitamin D deficient and 22.8% were vitamin D insufficient. The statistically significant risk factors for vitamin D deficiency identified were: number of AEDs, treatment with EIAEDs, low sun exposure, high body mass index (BMI) and a high frequency of epileptic seizures. After treatment, 25(OH)D mean level increased by 98.99% (regardless of EIAED use or being overweight). Significance . In our sample, more than half of the adults with epilepsy showed 25(OH) D deficiency. Patients on EIAEDs had lower 25(OH)D levels. A daily dose of 6, 670 IU cholecalciferol successfully led to the correction of 25(OH)D levels. A higher dose in obese patients or in patients taking EIAEDs may not be warranted and this should be considered in future guidelines for routine vitamin D deficiency treatment.